Hydrodynamic chromatography of silica colloids on small spherical nonporous silica particles - Aspanut, Z. (2009)
Hydrodynamic chromatography of silica colloids with 5 - 78 nm was investigated for spherical nonporous silica packed columns. Use of phosphate buffer as the eluent improved peak shape of silica colloids and allowed elution of the analytes at times relating to their sizes. The larger the diameter of the silica colloids, the faster the elution time was. Elution volumes of analytes were slightly increased with decreasing eluent flow rate, which may be due to more diffusion to narrower interstitial channels at lower flow rates. The separation column packed with 1.9-mu m nonporous silica achieved slightly better resolution than that with 3.1-mu n nonporous silica. Silica colloids were monitored based on turbidity using a UV detector, and larger signals were observed for larger silica colloids.